Improved Corrosion Protection Properties in Anodic Films Type Porous on 2024 T3 Aluminium Alloys Obtained by Pulse Reverse Plating. (2013)
This article presents the results of improvement in the electrochemical properties of porous type anodic films grown on aluminium alloy AA2024 T3, obtained with the techniques of direct current, pulsed direct current and reverse pulse current, through an electrolyte H2SO4 al 15% v/v. Morphological analysis was used atomic force microscopy and scanning electron microscopy allowing to identify the films obtained with inverse pulse current have a grain size smaller than those obtained by the two other deposition techniques. The evaluation of corrosion resistance in the films, we used electrochemical impedance spectroscopy and anodic polarization curves Tafel. These evaluation techniques established that the reverse pulse current deposition can generate deposits which increase the corrosion resistance of the anodic film.